2021
DOI: 10.1111/cod.13775
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis caused by tocopheryl nicotinate

Abstract: González de Arriba M. Should methyldibromo glutaronitrile in the baseline series be tested? Results of the skin allergy unit of a fourth-level hospital in Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…105 The vitamin E esterification seems to influence its immunogenic properties, since cross‐reactivity among different esters was not elicited by patch testing. 93 , 94 , 97 , 106 Given its increasing use in cosmetics and topical products, it has been suggested that vitamin E should be included in routine patch test series, 96 , 97 although the optimal concentration and vehicle are not known. Currently, there is no evidence that dietary vitamin E intake may induce a flare‐up of skin lesions in topically sensitized patients, although some authors recommend these patients to avoid vitamin E intake.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…105 The vitamin E esterification seems to influence its immunogenic properties, since cross‐reactivity among different esters was not elicited by patch testing. 93 , 94 , 97 , 106 Given its increasing use in cosmetics and topical products, it has been suggested that vitamin E should be included in routine patch test series, 96 , 97 although the optimal concentration and vehicle are not known. Currently, there is no evidence that dietary vitamin E intake may induce a flare‐up of skin lesions in topically sensitized patients, although some authors recommend these patients to avoid vitamin E intake.…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, tocopheryl seems to be a stronger sensitizer than tocopherol, and probably acts as an adjuvant, since contact allergy to vitamin E is often associated to other sensitizations such as to vitamin A, 78,80 glycyrrhetinic acid, 100 decyl oleate, 98 and Aloe vera 105 . The vitamin E esterification seems to influence its immunogenic properties, since cross‐reactivity among different esters was not elicited by patch testing 93,94,97,106 . Given its increasing use in cosmetics and topical products, it has been suggested that vitamin E should be included in routine patch test series, 96,97 although the optimal concentration and vehicle are not known.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations